Quantifying antioxidant activity of hydrophobic compounds using metal-mediated DNA damage - Gaertner, Andrea A. E.; Perron, Nathan R.; Anderholm, Heeren M. G.; Whitehead, Daniel C.; Brumaghim, Julia L. (Frontiers in Chemical Biology, 2025)
Cellular damage and death caused by oxidative stress by reactive oxygen species play an important role in disease development. Testing the ability of hydrophobic compounds to prevent radical-generated oxidative stress typically involves radical scavenging assays; however, these oxidative stress assays often do not accurately reflect biological outcomes. We present an in vitro assay that quantifiably evaluates the ability of hydrophobic compounds to prevent DNA damage, a biological endpoint that is linked to disease development. This gel electrophoresis assay enables evaluation of a wide range of hydrophobic compounds for metal-mediated hydroxyl radical damage prevention by using high-ethanol concentrations in electrophoretic conditions, and the effects of these high-ethanol conditions on iron- and copper-mediated DNA damage are established. This assay was used to compare the effects of metal-mediated DNA damage and its prevention by polyphenols, bipyridine, and selone antioxidant compounds as well as the radical scavenger edaravone. We also demonstrated that the well-studied glutathione peroxidase mimic ebselen and a group of ebselen derivatives prevent copper-mediated DNA damage with IC50 values in the 280–450 µM range. These same compounds do not inhibit iron-mediated DNA damage under similar conditions. This DNA-damage assay allows determination of antioxidant properties for hydrophobic antioxidants and drugs using a model system based on metal-mediated oxidative DNA damage, a primary cause of cell death.